Teacher’s Role in Designing the Competency Model of Professional Development - Đurić, Igor R.; Stanojević, Vladimir M. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
Professional development of teachers can be viewed as a heterotopia of simultaneous presence of different schools of opinion on teachers’ professional competence. The underlying premise of this research is that teachers’ professional development can simultaneously rely on various theoretical approaches, with boundaries between individual forms of teacher education being fluid, without the existence of a single view of the teaching profession that is regarded as fixed, unique, and correct. Alternative research paradigms and diverse schools of thought have not resulted in a single theory of teachers’ professional development that would be applicable in all educational systems. One of the solutions is for teachers to get involved, create, and adapt professional development programs to their needs, and to the needs of the institution, community, and the context of authentic school discourse. Teacher competence and professional identity explicitly require the involvement of teachers in the exchange of ideas (practitioner’s voice), taking into account the context in which they work and their experience, promoting reflexivity and research approach, balancing individual and community interests, and the like. One of the solutions pointed out in this paper is to emphasize the importance of the philosophy of professional development and the role of teachers in relation to this metalevel of the pedeutological field of pedagogy.